Methods of making investment decisions - J. A. Konopleva; O. N. Pakova; M. A. Aleksandrova (Вестник Северо-Кавказского федерального университета)
Introduction. In modern world, with the constant development of technology and changing market needs, investments play a signifi cant role for the effective operation of any organization and the state as a whole. Thanks to investments, the company's existing production processes and resources are being updated and expanded, which contributes to sustainable economic growth. Investments also have a significant impact on the volume of national income of the region, on the dynamics of which such macroeconomic parameters as gross domestic product, gross national product, national income and national wealth depend. Investments in the stock market play a significant role in generating future income and contribute to the creation of a portfolio of shares of different companies, allowing you to diversify risks and reduce the likelihood of losses.Goal. Analysis of the use of various methods of making investment decisions, allowing to study and select the most promising projects for investment, as well as to assess the risks and benefits of them. For effective activity, an investor needs to assess the profitability and expediency of investments, as well as choose the most optimal strategy to achieve their goals.Materials and methods. The methodological basis of the research includes a set of general scientific andspecial methods necessary for making investment decisions.Results and discussions. The methods of making investment decisions in the stock market have been studied. The conceptual framework is complemented by approaches to the definition of fundamental and technical analysis. The necessity of using these methods for making investment decisions in the stock market is substantiated. The scientific novelty of the work lies in the theoret ical substantiation of the mechanism and methods of making investment decisions in the stock market.Conclusion. The results of the study allowed us to identify the main advantages and disadvantages of using fundamental analysis for making investment decisions, as well as to determine the need for its use for successful activity in the stock market.